Inovasi Manajemen Pengelolaan dalam Mengembangkan Kualaitas PAUD - Munir, Misbahul; Subaeri, Abdul Holik; Alfian, Makhdar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
The aim of this research was to gain an understanding of the innovative practices in PAUD management at RA Darul Falah I Samarinda, which contribute to the enhancement of education quality. The study adopts a qualitative approach with a descriptive nature. The research participants were selected using convenience sampling and included administrators, teachers, students, and parents. Data collection involved observation, interviews, and documentation. The accuracy of the gathered information was verified through careful monitoring, active participation, and referencing. The findings reveal that management innovation in early childhood education encompasses the stages of planning, implementation, and evaluation. Planning involves formulating the institution's vision, mission, goals, annual and semester programs, as well as appropriately allocating human resources based on their abilities. The implementation of PAUD management commences with a SWOT analysis to identify strengths and weaknesses within the institution. Program and activity implementation should align with the existing conditions and planning documents, such as the RPP. Evaluating the achievement of success indicators for the PAUD program aligns with the desired profile of graduates from these early childhood education institutions. This evaluation can be accomplished through program evaluations of PAUD institution activities. It is essential to enhance PAUD management innovation to provide outstanding service to the community, particularly for early childhood education.